Awareness and Knowledge of Celiac Disease Among the General Population in Saudi Arabia - AlHussaini, Khalid I.; Alhusaini, Bassam Abdulaziz; Alzmamy, Saad Abdullah; Alfozan, Omar Abdulaziz; Alnayil, Abdulaziz Mohammed; Algannas, Turki Sulaiman; Alassaf, Turki Yazeed; Hakami, Osamah A. (Faculty of Medicine, Universitas Padjadjaran, 2024)
Celiac disease (CD) is an immune-mediated systemic disorder affecting nutrient absorption triggered by both environmental (gluten) and genetic factors. This study aimed to determine the level of awareness and knowledge of CD among the general population of Saudi Arabia. A community-based online cross-sectional study was conducted between August and October 2022 to examine the awareness regarding signs, symptoms, complications, and treatment of celiac disease. Data were collected and analyzed from 1,675 participants distributed across the five regions in Saudi Arabia. Analysis shows that 65.1% of the participants were familiar with the symptoms of celiac disease, and 49.6% confirmed that symptoms, blood tests, and endoscopy are the best way to diagnose celiac disease. The mean awareness score for the study participants was 71.8 (SD 13.9), with 5.2% of the participants needed a better level of awareness. Having a family history of celiac disease was an important predictor of having a higher level of awareness of celiac disease (p<0.001). The general public in Saudi Arabia demonstrates a moderate to high level of awareness of CD, emphasizing the need for extensive efforts to maintain high awareness of CD among the general public.